PENANGANAN JALAN DESA BERDASARKAN NILAI MANFAAT JALAN DI KECAMATAN KALIS KABUPATEN KAPUAS HULU - Adariu, -; Azwansyah, Heri; Mayuni, Siti (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2020)
The method needed for searching of data is using combination with interview, observation, and filling some IRAP questioannaire contains  value indicator and weight indicator. This analys is to get the benefits value of road which basically average of multiplication value indicator and weight indicator. This is very important because road is a vital infrastructure of accessibility for villagers. So that, the priority of road handling must make sure to give big benefits for villagers. Research shows that Nanga Raun street has higher benefits for number of road users as big as 20. Sepan Padang street has higher benefits in health sector as big as 17,75. Bahenap street has higher benefits in helath sector as big as 22,5. Beberuk street has higher benefits in health sector as big as 19,25. Kendualan street has higher benefits in health sector as big as 19,25. Landau Belaban street has higher benefits in health as big as 19. Riam Selimbau street has higher benefits in health as big as 19. In Nanga Raun Village, the first priority of road improvement is Arong street with higher benefits as big as 13,33. Then, the level of improvement priority in Nanga Raun Village is Tilung street.  In Bahenap Village, the level of road improvement is Bahenap street with benefits value as big as 14,2. The next priorities are  Sepan Padang street and Beberuk street. In Kensurai Village, the main level priority of road improvement is Riam Selimbau street with benefit value as big as 14,12. Next are Landau Belaban street and Kendualan street . Of all, the main priority of road improvement is Jalan Bahenap with benefit value as big as 14,2. The next priority is Riam Selimbau street with benefit value as big as 14,12,  Landau Belaban street with benefit value as big as 14,11, Sepan Padang street with benefit value as big as 14,03, Kendualan street with benefit value as big as 13,7, Beberuk street with benefit value as big as 13,65, Arong street with benefit value as big as 13,33. Meanwhile, the last priority is Tilung street with benefit value as big as 12,66.